#TITLE_ALTERNATIVE# - ADRIAT (NIM: 22412008); Pembimbing : Dr. Tri Wahyu Hadi; Dr. Dhani Herdiwijaya, RIZA
Cosmic rays is one of several factors from space that can influence global warming by the process of cloud formation. Cosmic rays are closely related with solar cycle through the solar wind and the solar magnetic field to deflect radiation manner. Cosmic rays can affect the formation of cloud cover through the ion-aerosol clear-water mechanism and ion-aerosol near-cloud mechanism. The role of cosmic rays as a source of energy is ionizing aerosols and charging near cloud which may accelerate the process of the formation of cloud condensation nuclei. We study the correlation of cosmic rays and global cloud cover following the ISCCP classification that can be divided into 9 types of cloud from year 1984 to 2008. We confirm that cosmic rays had high positive correlation with low cloud cover (for the types of Stratocumulus and Stratus). However we found that high cloud cover (for the type Cirrus) was also showed high correlation. Since year 2000, we showed that the correlation between cosmic rays and cloud cover are not clear. We suggested the low activity of the sun's polar magnetic field in the last decade for less than 150 microTesla may influence the global atmospheric electric circuit and the process of cloud formation.